การพัฒนาความสามารถการเขียนสะกดคำมาตราแม่ก กา ของนักเรียนออทิสติก ชั้นประถมศึกษาปีที่ 6 โดยใช้สื่อจอหรรษาพาสะกดร่วมกับแบบฝึกหัด - กาเรง, นุรดีญานา; หยดย้อย, รักษิณา; ฐิติพรวณิช, พรรณรอง (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2025)
การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อพัฒนาความสามารถการเขียนสะกดคำมาตราแม่ ก กา ของนักเรียนออทิสติก โดยใช้สื่อจอหรรษาพาสะกดร่วมกับแบบฝึกหัด 2) เพื่อเปรียบเทียบความสามารถการเขียนสะกดคำก่อนและหลังการใช้สื่อจอหรรษาพาสะกดร่วมกับแบบฝึกหัด กลุ่มตัวอย่างคือ นักเรียนออทิสติกชั้นประถมศึกษาปีที่ 6/3 ภาคเรียนที่ 1 ปีการศึกษา 2567 โรงเรียนสงขลาพัฒนาปัญญา จำนวน 5 คน คัดเลือกแบบเจาะจงจากนักเรียนที่ผ่านการคัดกรองโดยครูการศึกษาพิเศษ เครื่องมือวิจัยประกอบด้วย แผนการจัดการเรียนรู้ 12 แผน แบบฝึกหัดการเขียนสะกดคำ 10 ชุด แบบทดสอบการเขียนสะกดคำมาตราแม่ ก กา และสื่อจอหรรษาพาสะกดร่วมกับแบบฝึกหัด วิเคราะห์ข้อมูลด้วยค่ามัธยฐาน ค่าพิสัยควอไทล์ และทดสอบสมมุติฐานโดย The Wilcoxon Method-Pairs Signed-Ranks Test ผลการวิจัยพบว่า 1) นักเรียนออทิสติกมีความสามารถการเขียนสะกดคำมาตราแม่ ก กา อยู่ในระดับดีมากหลังการใช้สื่อจอหรรษาพาสะกดร่วมกับแบบฝึกหัด 2) ความสามารถการเขียนสะกดคำของนักเรียนหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 การวิจัยนี้ชี้ให้เห็นว่าสื่อและแบบฝึกหัดที่ออกแบบเฉพาะสำหรับนักเรียนออทิสติกสามารถช่วยพัฒนาทักษะการเขียนสะกดคำและการเรียนรู้ภาษาไทยได้อย่างมีประสิทธิภาพ This study aimed to: 1) enhance the spelling ability of autistic students in the "Mae Kor Ga" category using the " fun screen media " multimedia combined with spelling exercises and 2) To compare spelling ability before and after using the "Jor-Hansa Pa-Sakod" media combined with exercises. The sample group consisted of five Grade 6 autistic students from Songkhla Phatthanapanya School, selected purposively from students screened by special education teachers during the first semester of the 2024 academic year. The research tools included 12 learning plans, 10 spelling exercises, a spelling test for the "Mae Kor Ga" category, and the " Using fun screen media " multimedia. Data were analyzed using median, interquartile range, and hypothesis testing with the Wilcoxon Method-Pairs Signed-Ranks Test. The findings revealed that: 1) the spelling ability of autistic students in the "Mae Kor Ga" category improved to a very high level after using the multimedia combined with spelling exercises; 2) the students' spelling ability after the intervention was significantly higher than before, at the .05 statistical significance level. This research demonstrates that specially designed multimedia and exercises can effectively improve the spelling skills and language learning of autistic students.